2003
DOI: 10.1152/ajpheart.00438.2003
|View full text |Cite
|
Sign up to set email alerts
|

Protection afforded by ischemic preconditioning is not mediated by effects on cell-to-cell electrical coupling during myocardial ischemia-reperfusion

Abstract: The end-effectors of ischemic preconditioning (IPC) are not well known. It has been recently shown that transgenic mice underexpressing the gap junction protein connexin43 (Cx43) cannot be preconditioned. Because gap junctions allow spreading of cell death during ischemia-reperfusion in different tissues, including myocardium, we hypothesized that the protection afforded by IPC is mediated by effects on gap junction-mediated intercellular communication. To test this hypothesis, we analyzed the effect of IPC (5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 43 publications
1
47
0
Order By: Relevance
“…Because IP's cardioprotection is not dependent on the presence of gap junctions (23) and is not mediated by effects of cell-cell electrical coupling (29), it is unlikely that the loss of gap junctional Cx43 during aging is involved in the loss of cardioprotection by IP in the aged mice. Rather, the reduced content of mitochondrial Cx43, which is implicated in the trigger phase of preconditioning (17), may be related to the abolition of IP's cardioprotection in the Ͼ13-mo-old mice.…”
Section: Discussionmentioning
confidence: 99%
“…Because IP's cardioprotection is not dependent on the presence of gap junctions (23) and is not mediated by effects of cell-cell electrical coupling (29), it is unlikely that the loss of gap junctional Cx43 during aging is involved in the loss of cardioprotection by IP in the aged mice. Rather, the reduced content of mitochondrial Cx43, which is implicated in the trigger phase of preconditioning (17), may be related to the abolition of IP's cardioprotection in the Ͼ13-mo-old mice.…”
Section: Discussionmentioning
confidence: 99%
“…In the sarcolemma, Cx 43 is the constituent protein of gap junctions, and its inhibition prevents the spread of injury and extension of IS, 355 but whether this function is related to IPC is contentious. [356][357][358] However, with IPC, sarcolemmal Cx 43 phosphorylation and thus activity during the sustained ischemia is better preserved, 179 and this IPC-related Cx 43 activation may serve a protective function in attenuating cellular edema. 359 The predominant role of Cx 43 in cardioprotection, however, resides in the inner mitochondrial membrane.…”
Section: Connexin 43mentioning
confidence: 99%
“…This would result in less dephosphorylated Cx43 in gap junctions that could be acted on by PKC and subsequently become internalized, thereby preserving functional Cx43 in preconditioned hearts since preconditioning resulted in a marked preservation of Cx43 in gap junctions. A recent study in isolated rat hearts and in situ pig hearts found no effects of ischemic preconditioning on the ischemia-induced changes in electrical impedance, suggesting that intercellular electrical coupling is not important for protection (35). A very recent study by Li et al (36) found that PC protected wild-type isolated cardiomyocytes, obviously without forming gap junctions, but not Cx43-deficient myocytes, suggesting a volume regulating role of Cx43.…”
Section: Introductionmentioning
confidence: 98%